Usulan Perbaikan Pengiriman di PT. X untuk Mengurangi Lama Lembur Pekerja - Brian Farrel Ponda; I Gede Agus Widyadana (Jurnal Titra, 2020)
PT. X has a problem with overtime and delivery costs not being met. This problem is caused by PT. X did not have enough cars to meet his demand. For example, in shipments made in August 2019 where PT. X is 376,515 goods but the successful shipment was carried out by PT. X is only 200,743 items. This causes every car of PT. X has to ship more than once to be able to fulfill the shipment. But the distance of PT. X is far, unpredictable road conditions make workers PT. X has to work overtime every day, even the average worker's overtime in June, July and August is 3 hours. In addition to the average overtime duration overtime costs to be paid by PT. X in June, July and August 2019 is Rp 175,593,867 every month. Although the workers of PT. X overtime every day PT. X still can't fulfill his request. So from this problem the research was conducted to be able to provide proposals to PT. X to be able to reduce overtime costs and to meet deliveries.